Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas Terhadap Agretivitas Pajak pada Perusahaan Properti dan Real Estate yang terdaftar di BEI (2020-2022) - Ndraha, Irene Natalia; Siregar, Retnawati; Anindya, Desy Astrid (Jurnal Akuntansi Nommensen, 2023)
This research aimed to determine the effect of firm size, leverage, and profitability on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. The type of research used was quantitative with an associative causal nature. The population of this research included all property and real estate companies listed on the IDX from 2020- 2022. The sample selection used the purposive sampling method, and there were 20 companies that met the criteria, resulting in 60 observation data points. The data analysis techniques used were descriptive statistical analysis, classical assumption tests, and multiple linear regression analysis. Based on the t-test results, firm size had a significant value of 0.015 < 0.05 and a t-value > t-table, which was 2.512 > 2.00172, meaning that firm size had a positive and significant effect on tax aggressiveness. Leverage showed a significance value of 0.000 < 0.05 and a t-value > t-table, which was 4.549 > 2.00172, meaning that leverage had a positive and significant effect on tax aggressiveness. Profitability showed a significant value of 0.000 < 0.05 and a t-value > t-table, which was 7.804 > 2.00171, meaning that profitability had a positive and significant effect on tax aggressiveness. Based on the F-test results, firm size, leverage, and profitability simultaneously had a significance value of 0.000 < 0.05, meaning that firm size, leverage, and profitability had a positive and significant effect on tax aggressiveness.